Pengaruh Intensitas Kebisingan Terhadap Denyut Nadi Pekerja Sebelum Dan Sesudah Bekerja Di PT Iskandar Indah Printing Textile Surakarta - Retnani, Hendra (2016)
The noise in have cast by a machine weaving in PT. Iskandar Indah Printing Textile Surakarta can cause hearing loss, stress fatigue, stress work and eventually can be lowered labor productivity. The purpose of this research is to find the influence of noise intensity to the pulse workers before and after work in weaving. Research methodology it uses observational analytic with the approach cross sectional. Population this research is workers at the weaving as many as 40 people. Sampling with nonprobability sampling purposive sampling method about 32 people. Has research statistical test use wilcoxon. there are the influence of noise intensity to the pulse workers before and after work (p = 0,000)